2019
DOI: 10.1177/1934578x19862903
|View full text |Cite
|
Sign up to set email alerts
|

Antimildew Effects of Plectranthus amboinicus Leaf Essential Oil on Paper

Abstract: In this study, we evaluated the antimildew effects on paper of Plectranthus amboinicus (Lour.) Spreng leaf essential oil prepared through hydrodistillation. The oil was isolated with a Clevenger-type apparatus and then characterized through gas chromatography with flame ionization detection (GC-FID) and gas chromatography-mass spectrometry (GC-MS). A total of 43 compounds were identified, representing 99.5% of the oil. The main ingredients were carvacrol (50.0%), γ-terpinene (13.1%), and β-caryophyllene (11.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
11
1
2
Order By: Relevance
“…Scientifically, its endothelium-dependent hypotensive and vasorelaxant effects have been demonstrated [ 11 ], as well as its antimicrobial, antinociceptive [ 12 ], antitumor [ 13 ], anti-inflammatory [ 14 ] and antioxidant activities [ 15 , 16 ]. P. amboinicus is used for the treatment of colds, coughs, asthma, and diseases of the respiratory tract in general, as well as to treat headaches, fever, skin diseases, and gastrointestinal disorders [ 17 , 18 , 19 ]. Thus, because it is a well-known species and used by the population, many studies on its effects already exist and demonstrate its antimicrobial and antiviral activities in vitro [ 20 , 21 ], activity against respiratory and gastrointestinal disorders, anticonvulsant, antitumor [ 22 , 23 ], analgesic, anti-inflammatory, and antioxidant activities [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientifically, its endothelium-dependent hypotensive and vasorelaxant effects have been demonstrated [ 11 ], as well as its antimicrobial, antinociceptive [ 12 ], antitumor [ 13 ], anti-inflammatory [ 14 ] and antioxidant activities [ 15 , 16 ]. P. amboinicus is used for the treatment of colds, coughs, asthma, and diseases of the respiratory tract in general, as well as to treat headaches, fever, skin diseases, and gastrointestinal disorders [ 17 , 18 , 19 ]. Thus, because it is a well-known species and used by the population, many studies on its effects already exist and demonstrate its antimicrobial and antiviral activities in vitro [ 20 , 21 ], activity against respiratory and gastrointestinal disorders, anticonvulsant, antitumor [ 22 , 23 ], analgesic, anti-inflammatory, and antioxidant activities [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, because it is a well-known species and used by the population, many studies on its effects already exist and demonstrate its antimicrobial and antiviral activities in vitro [ 20 , 21 ], activity against respiratory and gastrointestinal disorders, anticonvulsant, antitumor [ 22 , 23 ], analgesic, anti-inflammatory, and antioxidant activities [ 24 , 25 ]. These two species are also used in culinary as flavorings and in the preparation of some foods [ 17 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 It was reported that essential oil production by P. amboinicus through hydrodistillation yielded only about 0.58 ± 0.03 mL/100 g dry weight of leaves. 7 Additionally, production of secondary metabolites from plant materials is also affected by geographical and environmental conditions, plant genetics and physiology as well as climate. 8 The ability of microbes in synthesising plant secondary metabolites drawn attention of many researchers as an alternative method.…”
Section: Introductionmentioning
confidence: 99%
“…Our research team has proven on numerous occasions the antifungal efficacies of various essential oils. 8,9 Cunninghamia lanceolata (Lamb.) Hook.…”
mentioning
confidence: 99%